Respuesta :

Answer:

○ [tex]z(x - 1) = -x^2 + 17x - 13[/tex]

Step-by-step explanation:

We are told that:

[tex]z(x)= 15x - x^2 + 3[/tex],

and told to find an expression for [tex]z(x - 1)[/tex].

In order to find [tex]z(x - 1)[/tex], we have to replace [tex]x[/tex] in the definition of [tex]z(x)[/tex] with [tex](x-1)[/tex]:

[tex]z(x - 1) = 15(x -1) - (x - 1)^2 + 3[/tex]

Now we can simplify:

⇒ [tex]z(x-1) = 15x - 15 - (x - 1)^2 + 3[/tex]      [Distributing 15 into the first brakets]

⇒ [tex]z(x-1) = 15x - 15 - (x^2 - 2x + 1) + 3[/tex]

⇒ [tex]z(x-1) = 15x - 15 - x^2 + 2x - 1 + 3[/tex]     [Distributing the minus sign]

⇒ [tex]z(x - 1) = 17x - x^2 -13[/tex]          [Combining like terms]

⇒ [tex]z(x - 1) = -x^2 + 17x - 13[/tex]

Therefore, the first option is the correct one.

ACCESS MORE